Analysis of Consumer Purchasing Patterns Using the Apriori Algorithm on Sales Transaction Data from Anak Panah Kopi Salatiga - Yoga Candra Adi Pratama; Christine Dewi (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Anak Panah Coffee is a café located in Salatiga, offering a menu of 12 items. To enhance consumer satisfaction, the management of Anak Panah Coffee has decided to implement a marketing strategy for promoting its products. Given the challenges faced by Anak Panah Coffee, this study aims to analyze consumer preferences to provide benefits both to the business and its customers. This research utilizes the Apriori algorithm, based on field data that can be calculated objectively. The results of applying the Apriori algorithm reveal two association rules with a minimum support of 30% and a minimum confidence of 60%. The first rule indicates that customers who purchase Sunny Go Coffee are likely to also purchase Mushroom Crispy, with a support value of 50% and confidence of 56%. The second rule suggests that customers who buy Crispy Mushrooms are likely to also purchase Sunny Go Coffee, with a support value of 50% and a confidence of 71%.